IMPLEMENTASI PENGELOLAAN ALOKASI DANA DESA BERDASARKAN PERATURAN PEMERINTAH NOMOR 43 TAHUN 2014 TENTANG PERATURAN PELAKSANAAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA (Studi Kasus di Desa Segati Kecamatan Langgam Kabupaten Pelalawan) - Sri Nabila; Dodi Haryono; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The management of village funds in empowering village residentsand to find out several factors that enable and hinder the management of villagefunds. This research uses sociological research methods. This activity was carriedout in Segati Village, LanggamDistrict, Pelalawan Regency, by conductinginterviews and observations to obtain data and information about interpretedvillage funds. Segati Village received a Village Fund budget of IDR2,571,968,300. In 2019, IDR. 2,809,007,000 in 2020, Rp. 2,442,927,000 in 2021and the Village Fund Allocation (ADD) budget in 2021 is Rp. 1,031,380,000. AndDistribution is carried out in 2 (two) stages, namely, the first stage 60% and thesecond stage 40%.The aim of this research is to determine the realization of VillageFund management in Segati Village, Langgam District, Pelalawan Regency. Thenumber of research informants was 5 people with the Village Head, VillageSecretary, Village Consultative Body, Management Activity ImplementationTeam, Subdistrict Head, as informants. data collection techniques usinginterviews and analysis.The research results show that the management of village fundscarried out by the village government has not been fully realized and needs to beimproved further. The suggestion in this research is that it is hoped that themanagement of Village Funds will put more emphasis on the provisions set so thatall sectors in the Village Fund Allocation management policy are implementedwell. As well as the Regional Government monitoring villages that do notimplement government policies regarding managing village funds properly, aswell as evaluating which villages use Village Fund Allocations but do not complywith the stipulated provisions so that they can be given warnings and sanctions sothat village fund management is realized properly.Keywords: Implementation, Management, Allocation of Village Funds